Probing Jovian decametric emission with the long wavelength array station 1. Issue 12 (1st December 2014) - Clarke, T. E.; Higgins, C. A.; Skarda, Jinhie; Imai, Kazumasa; Imai, Masafumi; Reyes, Francisco; Thieman, Jim; Jaeger, Ted; Schmitt, Henrique; Dalal, Nagini Paravastu; Dowell, Jayce; Ellingson, S. W.; et al.
Abstract: New observations of Jupiter's decametric radio emissions have been made with the Long Wavelength Array Station 1 (LWA1), which is capable of making high‐quality observations as low as 11 MHz. Full Stokes parameters were determined for bandwidths of 16 MHz. Here we present the first LWA1 results for the study of six Io‐related events at temporal resolutions as fine as 0.25 ms. LWA1 data show excellent spectral detail in Jovian DAM such as simultaneous left‐hand circular (LHC) and right‐hand circular (RHC) polarized Io‐related arcs and source envelopes, modulation lane features, S‐burst structures, narrow band N events, and interactions between S bursts and N events. The sensitivity of the LWA1 combined with the low‐radio‐frequency interference environment allow us to trace the start of the LHC Io‐C source region to much earlier CMLIII than typically found in the literature. We find that the Io‐C starts as early as CMLIII = 230° at frequencies near 11 MHz. This early start of the Io‐C emission may be valuable for refining models of the emission mechanism. We also detect modulation lane structures that appear continuous across LHC and RHC emissions, suggesting that both polarizations may originate from the same hemisphere of Jupiter. We present a study of rare S bursts detected during an Io‐D event and show that drift rates are consistent with those from other Io‐related sources. Finally, S‐N burst events are seen in high spectral and temporal resolution and our data strongly support the cospatial origins of these events. Key Points: LWA1 is a powerful new instrument for Jovian decametric study Io‐C source regions begin as early as CMLIII of 235 degrees at 11 MHz We present the first study of S bursts in an Io‐D emission event